East European Academies in Transition
XIX, 165 p.
Keywords: When the socialist regime in Central and Eastern Europe (CEE) was overthrown around the end of the eighties, beginning of the nineties, an overall transforma tion of whole societies started. Not only the political and the economic systems of these countries, but all societal sectors underwent deep changes. These changes presented opportunities, but they also spelled trouble. On one hand, getting rid of stifling political control and excessive bureaucratic regulation was something which most members of these societies desired. On the other, it be came apparent very soon that the necessary and long hoped-for rebuilding of the economy, education, health care, the mass media, and science, too, was strongly restricted by the scarcity of financial resources. After a short period, during which opportunities were energetically taken up in a spirit of hope, came a long and still lasting time of growing troubles and despondency. Only in a few of the CEE countries have some glimpses of hope become visible recently; and it re mains to be seen whether these signals are reliable. Until now, therefore, the transformation dynamics of all societal sectors in all of the CEE countries have primarily been troublesome. This is surely true for the post-socialist research systems. I The demise of the communist party's abso lute rule over society has allowed researchers the public expression and the pur suit of goals whose common denominator has been a greater self-regulation of scientific research according to its own criteria and logic.